Development of a Mandarin learning tool for children using speech recognition model - Wang, Yilin (Nanyang Technological University, 2024)
This project report explores the evaluation performance of speech recognition and generation models specifically for short Mandarin phrases and children's voices. It introduces a Mandarin learning application prototype framework that leverages these models, which have been finetuned to recognize nuances in children’s voice and short Chinese phrases. The primary goal of this study was to forge a developmental pathway for a learning tool designed to significantly enhance the educational experience of children. Presenting a tool framework focuses on improving pronunciation, intonation, and understanding of Chinese characters (汉字) through a structured pedagogical approach.